2005
DOI: 10.1007/s10865-005-4665-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol Concentrations and Non-Physical Aggression in Healthy Adults

Abstract: Although physical aggression in humans and other primates appears to be negatively associated with total serum cholesterol (TSC) concentrations, the relationship between other forms of aggression and TSC is less clear. A plurality of studies have reported a positive association, some have reported no association, and a minority have reported a negative association. Some authors have speculated that the variability in findings is attributable to inconsistencies in the definitions and measurement of what has oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Typically, individuals high in Neuroticism tend to have poorer self‐assessments of health (Goodwin & Engstrom, 2002; Wasylkiw & Fekken, 2002), and more often physical illness (Friedman, Kern & Reynolds, 2010; Lahey, 2009; Neeleman et al ., 2004), than individuals low in Neuroticism. Moreover, hostility, anger, and depression as facets of Neuroticism have been found to be risk factors for high cholesterol (Hillbrand, Waite, Rosenstein, Harackiewicz, Lingswiler & Stehney, 2005; Sutin, Terracciano, Deiana, et al ., 2010; Williams, Steptoe, Chambers & Kooner, 2011), hypertension (Rutledge & Hogan, 2002) and cardiovascular disease (Strike & Steptoe, 2004). However, there are mixed results for Neuroticism concerning body mass (Brummett, Babyak, Williams, Barefoot, Costa & Siegler, 2006; Roehling, Roehling & Odland, 2008; Sutin, Ferrucci, Zonderman & Terracciano, 2011) and mortality (Friedman et al ., 2010; Iwasa, Masui, Gondo, Inagaki, Kawaai & Suzuki, 2008; Shipley, Weiss, Der, Taylor & Deary, 2007; Terracciano, Lockenhoff, Zonderman, Ferrucci & Costa, 2008).…”
Section: Personality and Healthmentioning
confidence: 99%
“…Typically, individuals high in Neuroticism tend to have poorer self‐assessments of health (Goodwin & Engstrom, 2002; Wasylkiw & Fekken, 2002), and more often physical illness (Friedman, Kern & Reynolds, 2010; Lahey, 2009; Neeleman et al ., 2004), than individuals low in Neuroticism. Moreover, hostility, anger, and depression as facets of Neuroticism have been found to be risk factors for high cholesterol (Hillbrand, Waite, Rosenstein, Harackiewicz, Lingswiler & Stehney, 2005; Sutin, Terracciano, Deiana, et al ., 2010; Williams, Steptoe, Chambers & Kooner, 2011), hypertension (Rutledge & Hogan, 2002) and cardiovascular disease (Strike & Steptoe, 2004). However, there are mixed results for Neuroticism concerning body mass (Brummett, Babyak, Williams, Barefoot, Costa & Siegler, 2006; Roehling, Roehling & Odland, 2008; Sutin, Ferrucci, Zonderman & Terracciano, 2011) and mortality (Friedman et al ., 2010; Iwasa, Masui, Gondo, Inagaki, Kawaai & Suzuki, 2008; Shipley, Weiss, Der, Taylor & Deary, 2007; Terracciano, Lockenhoff, Zonderman, Ferrucci & Costa, 2008).…”
Section: Personality and Healthmentioning
confidence: 99%
“…In a study of participants in a cholesterol-lowering program, improvements in diet were associated with reductions in aggressive hostility and plasma cholesterol levels [32]. More recent studies have also reported a positive association of total serum cholesterol and non-physical forms of aggression (e.g., verbal aggression, hostility) among healthy adults [14]. In addition, total serum cholesterol was positively related to aggressiveness among college males who were not physically fit [33], which may reflect a similar sample as the adolescent boys in the current study who presented with unfavorable lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In light of empirical data suggesting that serum cholesterol levels may be positively associated with aggression [14] in adults and adolescents, we included serum lipid levels in the multivariate analyses. Two fasting venipunctures for serum lipids were drawn for the assessment of total cholesterol, HDL-C, and LDL-C as previously described [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After conducting multivariate analyses, the researchers found that both variables were associated with CAD, but hostility was a stronger predictor of CAD than Type A behavior. Furthermore, hostility has been linked to increased platelet aggregation (Shimbo et al, 2009), high blood pressure (Brondolo et al, 2009, Lazaro, Valdes, Marcos, & Guarch, 1993, and elevated total serum cholesterol (Hillbrand et al, 2005)-all factors believed to be related to poor cardiovascular health.…”
Section: Hostility and Healthmentioning
confidence: 99%